Application of analytical ultracentrifugation in gravitational sweep mode coupled with turbidity detection for analyzing polydisperse emulsions of aged biodiesel and alkanes - Türck, Julian; Schilling, Kristian; Walter, Johannes; Schmitt, Fabian; Lichtinger, Anne; Türck, Ralf; Ruck, Wolfgang K. L.; Krahl, Jürgen (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Alternative fuels offer the possibility of reducing greenhouse gas (GHG) emissions with the help of the existing fleet. As a result, the introduction of new drop-in fuels leads to more complex interactions between the fuel components. Fuel aging is an important parameter in fuel design, as it describes the storage stability of the fuels. Generally, fuel aging increases polarity while simultaneously widening the polarity gap between the various fuel components. This gradient in polarity fosters the formation of emulsions, which can occur both within the fuel itself and, later, in lubricating oils (engine oils) during engine operation. The aim of this work was to find an analysis method for the investigation of emulsions of aged fuels (in this case biodiesel) and alkanes (HVO: hydrogenated vegetable oils and BO: base oil) without water or stabilizers. The difficulty here was to reproducibly measure a turbid, polydisperse and unstable system. The sedimentation velocity of HVO system was twice as high as that of the BO system. Droplet size distributions of biodiesel–HVO (BD–HVO: 500 to 5500 nm) and biodiesel–BO (BD–BO: 400 to 3750 nm) could be determined with high resolution using an analytical ultracentrifugation setup with multi-wavelength turbidity detection coupled to gravitational sweep experiments. The influence of polar molecules such as isopropylidene glycerol (solketal) and 1-octanol on the emulsions was further investigated considering the percentile size values of the respective distributions. This methodology therefore has the potential to provide a deeper understanding of the physical processes that influence the aging of engine oil.